2007
DOI: 10.1016/j.scienta.2006.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Water relations and yield of lysimeter-grown strawberries under limited irrigation

Abstract: The effects of partial root-zone drying (PRD), as compared to deficit irrigation (DI) and full irrigation (FI), on strawberry (cv. Honeoye) berry yield, yield components and irrigation water use efficiency (WUE I ) were investigated in a field lysimeter under an automatic rain-out shelter. The irrigation treatments were imposed from the beginning of flowering to the end of fruit maturity. In FI the whole root zone was irrigated every second day to field capacity viz. volumetric soil water content (u) of 20%; w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 18 publications
9
42
2
1
Order By: Relevance
“…Previous studies also showed that fruits from strawberry plants that received full irrigation had a higher water content and greater berry fresh weight than fruits from plants grown under reduced irrigation (Liu et al, 2007;Terry et al, 2007;Bordonaba, Terry, 2010;Ipek et al, 2014). Water stress has a great influence on the plant photosynthetic capacity of strawberry (Mao et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies also showed that fruits from strawberry plants that received full irrigation had a higher water content and greater berry fresh weight than fruits from plants grown under reduced irrigation (Liu et al, 2007;Terry et al, 2007;Bordonaba, Terry, 2010;Ipek et al, 2014). Water stress has a great influence on the plant photosynthetic capacity of strawberry (Mao et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, to limit the amounts of water used for several horticultural crops, water deficit irrigation has been seen as a potential alternative for new cultivation systems (Bordonaba, Terry, 2010). In strawberry plants regulated deficit irrigation technique is generally associated with reduction in fruit size and yield; (Liu et al, 2007). Despite this fact, other attributes, related to fruit quality increased (Terry et al, 2007;Heiadari, Golpayegani, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A rapid decrease of leaf water potential was found in pot-grown strawberry plants under water deficit (Blanke and Cooke, 2006). In field studies, fruit yields of strawberry failed under soil waterdeficit conditions (Krüger et al, 2002;Liu et al, 2007;Terry et al, 2007;Kim et al, 2007). Previous reports found many changes in physiology and biochemistry of strawberry in response to stress.…”
Section: Introductionmentioning
confidence: 97%
“…DI, also known as regulated deficit irrigation (RDI), is an irrigation technique whereby crops are exposed to lower amounts of water and the minor stress experienced by the plant is expected to have a minimal effect on the yield (English & Raja, 1996). In strawberry plants, however, this technique (DI) is generally associated with reduction in fruit size and yield (Blatt, 1984;Krüger et al, 1999;Liu et al, 2007;Serrano, Carbonell, Savé, Marfà, & Peñuelas, 1992). Nevertheless, a recent study demonstrated that DI of strawberry cv.…”
Section: Introductionmentioning
confidence: 99%